2003
DOI: 10.1051/apido:2003033
|View full text |Cite
|
Sign up to set email alerts
|

In vitro secretion of ecdysteroid-dependent proteins and of a 70 kDa subunit reactive to anti-prophenoloxidase serum by Apis mellifera integument

Abstract: -A tissue culture approach was used to monitor changes in protein secretion by integuments from Apis mellifera along the pupal stage. A dramatic change in epidermal protein secretion was correlated with the variation in endogenous ecdysteroid from a low level at the beginning of the pupal stage to a maximum level in the middle of this stage. Only a fraction of these proteins, however, turned out to be directly regulated by ecdysteroids when we exposed cultured integument to 20-hydroxyecdysone. An antiserum rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Initially it was thought that the presence of PO in integument was due to its transportation from the hemolymph, as proposed by Ashida and Brey (1995), and Asano and Ashida (2001a, b) in their studies on the cuticular PO from B. mori. However, the demonstrated de novo synthesis of the 70 kDa protein reactive to anti-PO in incubations of honey bee integuments strongly suggested that honey bee epidermis synthesizes a genuine PO of molecular mass and immunological properties identical to that of hemolymph (Colonello et al, 2003). These data are now reinforced by the demonstrated presence of proPO transcripts in integument (this paper), showing that the epidermis is actively involved in the proenzyme synthesis, although could also be the repository of ProPO synthesized in hemocytes.…”
Section: Article In Pressmentioning
confidence: 54%
See 1 more Smart Citation
“…Initially it was thought that the presence of PO in integument was due to its transportation from the hemolymph, as proposed by Ashida and Brey (1995), and Asano and Ashida (2001a, b) in their studies on the cuticular PO from B. mori. However, the demonstrated de novo synthesis of the 70 kDa protein reactive to anti-PO in incubations of honey bee integuments strongly suggested that honey bee epidermis synthesizes a genuine PO of molecular mass and immunological properties identical to that of hemolymph (Colonello et al, 2003). These data are now reinforced by the demonstrated presence of proPO transcripts in integument (this paper), showing that the epidermis is actively involved in the proenzyme synthesis, although could also be the repository of ProPO synthesized in hemocytes.…”
Section: Article In Pressmentioning
confidence: 54%
“…Recently, we showed that an antiserum developed against the honey bee hemolymph PO (anti-PO antiserum) was able to cross-react with a protein from thoracic integument, which was similar in molecular mass (70 kDa, as determined by SDS-PAGE) to the enzyme found in hemolymph (Colonello et al, 2003). Initially it was thought that the presence of PO in integument was due to its transportation from the hemolymph, as proposed by Ashida and Brey (1995), and Asano and Ashida (2001a, b) in their studies on the cuticular PO from B. mori.…”
Section: Article In Pressmentioning
confidence: 99%
“…The molecular mass of the single A. mellifera PO (70 kDa) closely corresponds to that of the cleaved protein (74 kDa) deduced from the nucleotide sequence (this paper). Antibodies raised against the hemolymph PO detected this protein also in integument (Colonello et al, 2003), suggesting that in addition to its well-known function in the defense against invading agents, this enzyme also participates in cuticle pigmentation and sclerotization. The coincidence between the initiation and intensification of melanin deposition into the pupal cuticle and the increase of both, PO specific activity (Zufelato et al, 2004) and amount of AmproPO transcripts (this paper), cause this consideration to be quite pertinent.…”
Section: Article In Pressmentioning
confidence: 98%
“…Tanto a atividade da enzima como a abundância do produto de transcrição gênica evidenciaram correlação com o grau de maturação cuticular, sugerindo um papel não usualmente atribuído às tirosinases na formação do exoesqueleto Lourenço et al, 2005). A presença da proteína precursora, a profenoloxidase, foi confirmada em tegumentos cultivados in vitro (Colonello et al, 2003). Também foram estabelecidos os perfis de proteínas estruturais do tegumento nas diversas fases que caracterizam o desenvolvimento farato do adulto (Santos et al, 2001).…”
Section: Os Diferentes Estágios Do Desenvolvimento Pré-imaginal Das Cunclassified